Vacuolar SPX-MFS transporters are essential for phosphate adaptation in plants. (2nd August 2016) - Liu, Jinlong; Fu, Shaomin; Yang, Lei; Luan, Mingda; Zhao, Fugeng; Luan, Sheng; Lan, Wenzhi
ABSTRACT: To survive in most soils in which inorganic phosphate (Pi) levels are limited and constantly changing, plants universally use the vacuoles as cellular Pi "sink" and "source" to maintain Pi homeostasis. However, the transporters that mediate Pi sequestration into the vacuoles remain unknown. Recently, we and other 2 groups independently identified the members of SPS-MSF family as the candidates for tonoplast Pi transporters in Arabidopsis thaliana and Oryza sativa . We and Liu et al. demonstrated that one of SPS-MSF member, VPT1 (Vacuolar Phosphate Transporter 1), also named as PHT5;1 (Phosphate Transporter 5;1), plays a predominant role in Pi sequestration of vacuoles in Arabidopsis . Here we show that vpt1 mutants and VPT1-GFP overexpressing lines displayed sensitive to Pi stress under the hydroponic system containing the medium with low iron, supporting that VPT1 is essential for Arabidopsis to adapt phosphate stress.